Differentiated Learning Strategies to Accommodate Diversity of Learning Styles in Inclusive Classrooms_VOL 2. No 1 - Abdul Ghani (Innovative Pedagogy and Education Studies, 2024)
This study examined the effectiveness of differentiated learning strategies in accommodating diverse learning styles within inclusive classroom settings. A mixed-methods research design was implemented involving 90 fourth-grade students from three inclusive elementary schools in Surabaya, Indonesia. Participants were categorized based on VARK learning style assessments (Visual, Auditory, Reading/Writing, Kinesthetic). The experimental group (n=45) received differentiated instruction tailored to individual learning styles for twelve weeks, while the control group (n=45) received standard instruction. Academic achievement was measured through pre and post-tests, and student engagement was assessed using observation protocols. Data analysis employed paired sample t-tests and thematic analysis (p<0.05). Results indicated that students receiving differentiated instruction achieved significantly higher academic scores (M=82.67, SD=7.45) compared to the control group (M=71.34, SD=8.92) with t(88)=6.89, p<0.001, d=1.35. Specifically, kinesthetic learners showed the greatest improvement (47.3% increase), followed by visual learners (39.8% increase). Qualitative findings revealed enhanced student participation, self-confidence, and classroom inclusivity. Teachers reported increased satisfaction with differentiated approaches despite initial implementation challenges. Differentiated learning strategies effectively accommodate learning style diversity in inclusive classrooms, promoting equitable educational opportunities and improved academic outcomes for all students.